Training Working Memory of Children with and without Dyslexia - Claudia Maehler; Christina Joerns; Kirsten Schuchardt (MDPI AG, 2019)
For the future school performance of a child in the fields of literacy and numeracy, the operational efficiency of working memory is a central predictor. Children affected by dyslexia exhibit specific deficits in the functions of working memory. A software application for elementary school-age children has been specifically developed for this study, attempting to improve the working memory’s operational efficiency. Based on Baddeley’s model of working memory (1986), the phonological loop, the visuo-spatial sketchpad, and the central executive were trained in 18 sessions over a period of six weeks. The group of test subjects undergoing this training was composed of third-graders, of which 43 were and 27 were not affected by dyslexia. The untrained control group was made up of 41 third-graders with dyslexia and 28 without dyslexia. While the short-term effects of the program could not be proven, the present analyses focus on long-term effects. The results obtained from a pre-test/follow-up design reveal that no long-term increases in performance regarding phonological and central executive working memory could be confirmed. Only the visuo-spatial Corsi block span exhibited a training effect over a period of three months. Additionally, training did not show any long-term effect of performance improvement, not even for a subgroup of children with dyslexia and an especially low working memory performance. Thus, even after this study, the question whether working memory can be trained or not remains partly unanswered but leaves us predominantly pessimistic.